Development and quality properties assessment of fish ball prepared from milkfish supplemented with sorghum-dried distillers’ grains - Shu Chen Hsu; Chin Fu Chou (Applied Food Research)
Milkfish balls (MF) are important processed fish products that are popular among consumers and have the potential for development. However, the characteristics of MF are significantly affected by ingredients in the ra materials. Therefore, in the present study, the impact of sorghum-dried distillers’ grains (SDDG) incorporated into MF on the quality characteristics was assessed. Results showed that on comparison with the control group (T-0, 0 % SDDG) (1.33 %, 0.87 %, 0.46 %, 2.18, 238.50 gf, 169.32 gf and 5.99 mJf), the incorporation of SDDG into MF significantly increased cooking loss (2.37–16.57 %), water loss (1.57–10.27 %), fat loss (0.80–6.29 %), a-value (4.17–5.85), hardness (279.83–631.83 gf), gumminess (202.58–455.20 gf) and chewiness (6.14–15.66 mJf) (p < 0.05). Conversely, the incorporation of SDDG was also able to decrease pH value (5.45–5.87), l-value (39.48–53.07), b-value (6.97–9.58), springiness (0.35–0.41) and cohesiveness (0.64–0.72) significantly, when compared to the control group (5.93, 64.47, 17.49, 0.42 and 0.72) (p < 0.05). However, the addition of SDDG did not affect water-holding capacity (17.49 %, 17.23–17.89 %) (p > 0.05). The results suggest that SDDG significantly influences MF quality and contribute to improving the economic value of processed fish food products.